Chapter Massimo Quaini, bricoleur. Su un libro che avrebbe potuto essere e non fu - TANCA, MARCELLO (Territori, 2021)
This article contains the text of an e-mail I received from Massimo Quaini in 2017. Through this mail he was answering to my invitation to participate in the fourth edition of "Dialoghi tra geografia e filosofia", a 'dialogic' seminar I have been organizing since 2014 to enhance the discussion between geographers and philosophers. Due to his illness, unluckily he was unable to attend the conference but he wrote me an e-mail in which he invited me to write a book together, four-handed. This e-mail is one of the last documents ever written by Quaini: here we have many of his landscape ideas, as well as many thoughts on the identity and the future of geography, and much more. For this reason I thought making this mail public could be the best way to honour his memory.